Excess mortality in the myelodysplastic syndromes. Issue 2 (7th December 2016) - Nomdedeu, Meritxell; Pereira, Arturo; Ramos, Fernando; Valcárcel, David; Costa, Dolors; Arnan, Montserrat; Calvo, Xavier; Pomares, Helena; Luño, Elisa; Díaz‐Campelo, María; Collado, Rosa; de Paz, Raquel; et al.
Abstract: Myelodysplastic syndromes (MDS) are the commonest hematologic malignancies in the elderly. Since many patients with MDS actually die from age‐related ailments, the very disease burden of MDS remains largely unknown. This registry‐based study was aimed at investigating the excess mortality attributable to MDS. We analyzed 7, 408 adult patients diagnosed with primary MDS from 1980 to 2014. Excess mortality was estimated by comparing the patients' survival with that expected in the matched general population. Median age of patients was 74 years, 58% were males, and 65% belonged to the lower risk categories of the Revised International Prognostic Scoring System (IPSS‐R). Excess mortality accounted for three‐fourths of the all‐cause mortality and was mainly driven by factors unrelated to leukemic transformation. Excess mortality increased with the IPSS‐R risk category [Incidence rate ratio (IRR): 2.1, 95% CI: 1.9–2.3; P  < .001]. Older age and male sex retained an independent association with higher excess mortality after discounting demographic effects. Excess mortality increased in the most recent periods just in the higher risk IPSS‐R categories (IRR: 1.2; 95% CI: 1.1–1.3 when comparing periods 2007–14, 2000–06, and 1980–99). In conclusion, MDS carry a significant excess mortality, even in the lower risk categories, that is mainly driven by factors unrelated to leukemic transformation, and increases with older age, male sex, and poorer risk categories. Excess mortality has increased in recent years in the higher risk patients, which might be ascribed to a parallel increase in age‐related comorbidities. Our results claim for more comprehensive treatment strategies for patients with MDS. Am. J. Hematol. 92:149–154, 2017. © 2016 Wiley Periodicals, Inc.